The Effect of Profitability, Leverage, and Digital Transformation on Environmental, Social, and Governance (ESG) Performance in Manufacturing Companies - Putri, Haurelia Syahnifa; Mulyantini, Sri (Finance : International Journal of Management Finance, 2025)
This study aims to examine the relationship between Profitability, Leverage and Digital Transformation on ESG Performance in manufacturing companies. The writer used 42 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023 which had passed the purposive sample criteria. This Research Method using logistic regression analysis testing and Eviews 13 data processing application. The results showed that Profitability has an effect on ESG performance while Leverage and digital transformation have no effect on ESG performance.